EMPOWERING FARMERS THROUGH THE UTILIZATION OF OWL HOUSE INNOVATION (RUBUHA) IN CONTROLLING RICE FIELD RAT PESTS FOR FOOD SECURITY - Setia Budi; Lukman; Eva Wardah (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Rat (Rattus spp.) pest infestations are a major constraint to rice productivity in Pidie Jaya Regency, Aceh, with potential losses reaching 60–70% and even crop failure. Conventional methods currently used by farmers, such as chemical rodenticides and electric traps, have proven ineffective in the long term and have negative ecological impacts. This Community Service (PKM) activity introduced the Owl House (RUBUHA) innovation as a sustainable biological control approach by involving farmer groups in Meurah Dua Sub District. The implementation method includes five stages: socialization, theoretical and practical training (30%–70%), application of RUBUHA in demonstration plots, intensive mentoring, and development of sustainability strategies. Evaluation of farmer knowledge was conducted through pre- and post-tests, while productivity impacts were measured based on harvest data before and after technology implementation. The implementation results showed an increase in rice productivity from 6.1 tons/ha to 7.2 tons/ha, with an estimated additional income of IDR 5–6 million/ha. Farmers' knowledge and skills increased by 70%, indicating the success of learning-by-doing-based technology transfer. In addition to economic benefits, the implementation of RUBUHA also reduces the use of chemical rodenticides, thus positively impacting the environment. The results of this PKM are not only relevant in supporting local food security and farmer welfare but also align with the achievement of the SDGs. Replication Innovation Rubuha to other regions is recommended as part of a community-based Integrated Pest Management strategy.